The Students’ Ability In Comprehending English Descriptive Text of The Eighth Grade Students at SMPN 28 Tanjung Jabung Timur - Muhammad Arvan (Cahaya Ilmu Cendekia Publisher, 2021)
Tujuan Penelitian: This research has a purpose to analyze the students’ ability in comprehending English descriptive text of the eighth grade students at SMPN 28 Tanjung Jabung Timur. Metodologi: This research is classified as a descriptive research type using quantitative methods. The population of this study were students of class VIII SMPN 28 Tanjung Jabung Timur. The samples used were class 8A and class 8B, totaling 42 people. The research instrument used was a reading test to measure or analyze their ability to understand English descriptive texts. The data analysis technique used was tabulated data obtained from the reading test, calculated in the assessment classification, calculated in the percentage of data within the range of 0% - 100%, explained the results, and concluded from the research results. Temuan Utama: The findings of this study indicate that the students' ability in understanding English descriptive texts is low. Keterbaruan/Keaslian dari Penelitian: The novelty of this research is to analyze students' ability to understand English descriptive text.